Social Function of Maxim to Present “Coming of Age” Value through Bildungsroman Novel Translation Entitled Norwegian Wood by Haruki Murakami - Gandis Octya Prihartanti (Masters in English Education, The Directory of Postgraduate Program,Universitas Muhammadiyah Malang, 2021)
This study aims to identify maxim utterance in Bildungsroman novel entitled Norwegian Wood by Haruki Murakami as well as translation technique used. Another purpose is to know the value of “coming of age.” This is a qualitative study which means the data were collected through document review from two sources; research object and rater assessment. The result shows that there are nine translation technique applied, they are: Established Equivalent, Amplification: Explicitation and Paraphrase, Reduction, Variation, Creation Discursive, Modulation, Paraphrase, Pure Borrowing, Generalization, Linguistic Compression: Implicitation. Regarding to quality of accuracy, acceptability, and readability, the following findings are shown as follows: accurate: 80%, less accurate 10%, not accurate 10%, acceptable 100%, less acceptable 0 %, not acceptable 0 %, readable 100 %, less readable 0%, and not readable 0%.